Epidemiological significance of poultry litter for spreading the antibiotic-resistant strains of Escherichia coli. Issue 3 (1st September 2016) - Ljubojević, D.; Puvača, N.; Pelić, M.; Todorović, D.; Pajić, M.; Milanov, D.; Velhner, M.
Abstract : The relationship between the use of antibiotics and the presence of antibiotic resistant strains of E. coli, as well as antibiotic residues in poultry litter, mainly due to irregular use of antibiotics is reviewed in the present paper. The aim of this review is to examine the existing problem of poultry waste management and how it can impact agricultural ecology and economy. Actions such as monitoring and reporting incidents of disease outbreaks in the future should provide an outline of how to improve and implement suitable regulations.